Determining Breast Density in Patients with Metabolic Syndrome: A Cross Sectional Study - Hamta Taheri Sarvetamin (Journal of Pharmacy and Bioallied Sciences)
Introduction and Objective: Breast density is considered a primary factor of mammography sensitivity, which serves as an optimal tool for breast cancer screening, given the potential role of metabolic syndrome in increasing breast density. Therefore, this study aimed to determine breast density in patients with this syndrome. Methods and Methodology: This cross-sectional study was conducted on 196 premenopausal women divided into metabolic syndrome and healthy groups. Mammograms were performed, and breast density was measured based on the ACR standard definition. The collected data were analyzed using the Chi-square test and SPSS software version 18. Findings: In the control group, 24% were classified as A, 28% as B, 24% as C, and 24% as D. In the experimental group, 20.8% were classified as A, 8.3% as B, 41.7% as C, and 29.2% as D (P value = 0.001). There was no significant difference between the frequency of lesions requiring further evaluation and benign lesions (P value > 0.05). Conclusion: Based on the results, metabolic syndrome may increase mammographic density.